Email Spam Detection Using a Hybrid Approach of Feedforward Neural Network and Penguin Optimization Algorithm - Layth Al-busultan (Wasit Journal of Computer and Mathematics Science)
The electronic communication of today is beset by unwanted junk messages. These are not just a nuisance; they waste our time and energy and clog up our inboxes, which are supposed to be, in many ways, our digital front doors. But how do we keep them from coming? Well, as today's article makes clear, the situation is hardly straightforward. There are various methods that can be used, both traditional and modern, and each has its own set of pros and cons. One method, however, stands out in today's article as one that we think might work well in practice, the good old-fashioned neural network.